Effects of Different Excitation Parameters on Mechanized Harvesting Performance and Postharvest Quality of First-Crop Organic Goji Berries in Saline–Alkali Land - Yuchuang Liu; Jiahui Liu; Jian Zhao; Fanyu Wang; Hongye Zhang; Xiaokang Su; Yichun Sun; Jia Liu; Dong Zhao (Agriculture, 2025)
Efficient and low-loss harvesting methods are crucial for preserving the postharvest quality of the first crop of goji berries grown in saline–alkali soils. However, as a brittle horticultural fruit rich in diverse bioactive compounds, goji berries are highly vulnerable to mechanical damage during harvesting, which adversely affects their storability and subsequent processing. To address this challenge, a multi-degree-of-freedom vibration model was developed based on the growth characteristics of first-crop organic goji berry fruit-bearing branches in the Qinghai region. The dynamic response of the branches under various excitation conditions was simulated, and the effects of excitation position, frequency, force amplitude, and phase angle on the fruit detachment rate, impurity rate, and breakage rate were systematically analyzed. Based on both the simulation and experimental results, a response surface methodology (RSM) was employed to optimize the picking parameters. The results of the field experiment showed that under the optimal conditions of vibration excitation in the ripe fruit area, a frequency of 5.7 Hz, an amplitude of excitation force of 0.27 N, a phase angle of 135°, a fruit picking rate of 97.58%, a miscellaneous content rate of 5.12%, and a breakage rate of 7.66% could be realized. The results of this study help to maintain the postharvest quality of first-crop goji berry fruits in saline–alkali land, and also provide a theoretical basis and practical reference for the optimization of first-crop goji berry harvesting equipment.